Catatan Perjuangan Bahasa Bali dalam Kurikulum 2013 - I Nyoman Suka Ardiyasa (Jurnal Kajian Bali (Journal of Bali Studies), 2012)
AbstractThis article chronicles recent efforts to maintain Balineselanguage instruction in Balinese schools in response to the2013 National Curriculum, which was to replace the formerCompetency-Based Curriculum (Kurikulum BerbasisKompetensi). The new curriculum aimed to integrate locallanguage instruction into the module for ‘local content/artsand culture’ (muatan lokal/seni budaya). It is important tonote, however, that Balinese were not alone in reacting tothe ‘disappearance’ of regional languages from the draftCurriculum for 2013. Rather, their desire to ensure thecontinuity of instruction in Balinese found parallels in otherregions — such as Central Java and Sundanese-speakingparts of West Java — where similar struggles were afootto uphold the teaching of local languages. It was fearedthat the younger generation would increasingly abandonregional languages should they no longer be taught inschools. Having laid out some of the consequences thatwould follow from abandoning the teaching of Balinese inschools, the article concludes with a series of suggestionstoward the preservation of the Balinese language.